Theory and computations of two-photon absorbing photochromic chromophores - Masunov, Artem E.; Mikhailov, Ivan A. (European Journal of Chemistry, 2010)
Exponential growth in information technology generates ever increasing amounts of data, making recording density of the storage media crucially important. Two-photon absorption was proposed as a basis for high-density multi-layer technology for optical memory and logic devices. This technology suggests to use polymers, doped with photochromic compounds that undergo a reversible photoinduced isomerization, or photoswitching. In this review we consider recent theoretical works and benchmarking studies of the DFT-based methods, capable to predict two-photon absorption (2PA) and photochemical activity, Next we review the applications of these methods to design a prototype molecule that combines the photon-mode recording property of photochromic compounds with large 2PA cross-section. We conclude that a posteriori Tamm-Dancoff approximation to the second order CEO approach in Density Functional Theory is the powerful tool for both quantitative predictions and qualitative understanding of the excited state processes in photophysics and photochemistry. We also emphasize general principles for the rational design of a two-photon operated photoswitch.